Sero-prevalence of Schistosoma species in cattle in Maiduguri Metropolis and Jere Local Government Areas of Borno State, Nigeria - Hambali, Idris Umar; Adamu, Nuhu Bala; Ahmed, Musa Isiaku; Bokko, Paul; Mbaya, Albert Wulari; Tijjani, Abdulyekeen Olawale; Biu, Abdullai Abubakar; Jesse, Faez Firdaus Abdullah; Ambali, Abdul-Ganiyu (Journal of Advanced Veterinary and Animal Research, 2016)
Objectives: This study was designed to investigate the Sero-prevalence of Schistosoma species in cattle in Maiduguri Metropolis (MMC) and Jere Local Government Areas (LGAs) of Borno State, Nigeria. Materials and Method: Blood samples (n=200) from cattle were collected using a multistage sampling technique; 100 samples each were collected from MMC and Jere LGAs, respectively. The samples were subjected to screening for Schistosoma antibodies using Enzyme Linked Immunosorbent Assay (ELISA). Age, sex, breed and location of cattle were recorded. Results: The overall prevalence of Schistosoma infection among cattle in MMC and Jere LGAs was 10%. Jere LGA had a prevalence rate of 14% and MMC had 6%. At the ward levels, Custom Area in Jere LGA had the highest number of Schistosoma positive (50%). Out of 103 female and 97 male cattle screened, the prevalence of Schistosoma infection in female and male were 9.71% (n=10/103) and 10.31% (n=10/103). Out of the 177 serum samples from cattle aging >1-year (adult) examined, 16 (9.04%) were positive, while only 4 (17.39%) out of 23 serum samples from cattle aging <1-year (young) were positive. Out of the eight (8) breeds screened, the highest number of cases was recorded in Kuri breed (16.22%). This was followed by Sokoto Gudali (10.9%) breed. The prevalence in other breeds was as follows: Abore- 10%, Red Bororo- 5.26%, and White Fulani- 6.67%. Conclusion: It is concluded that schistosomiasis in cattle was prevalent in MMC and Jere LGAs of Borno State. A regular checking program is suggested to constantly check out whether the prevalence rate is increasing, so that effective control measures can be strenthened. http://dx.doi.org/10.5455/javar.2016.c132